Informal Practices of Inequality in Recruitment in Finland - Koivunen, Tuija; Ylöstalo, Hanna; Otonkorpi-Lehtoranta, Katri (Nordic Journal of Working Life Studies, 2015)
In this article, we explore the policies and processes of selection and recruitment from the perspective of equality. Focusing on tacit ideas of the ‘ideal worker,’ ideal recruitment, and selection that direct the recruitment process, we examine the ways in which implicit ideas and recruitmentrelated settings of daily interaction become informal practices of inequality. In this analysis, we rely on the conceptual framework of inequality regimes. The qualitative analysis of the semi-structured interviews focuses on the categories of gender, ethnicity, and age. We identified three categories of informal practices of inequality, which we have named as recruitment by the book, relocation of responsibility, and recruiting by addressing the difference. The findings suggest that although recruiters follow the legislation concerning equal treatment in recruitment, they do so because they want to avoid problems and possible litigation rather than because they are committed to promoting equality as an end in itself. However, equality promotion requires that gender, ethnicity, and age equality is itself the goal. If equality serves other goals, such as avoiding litigation or boosting business, the everyday practices of recruitment may turn into informal practices of inequality.